The Calais garrison : war and military service in England, 1436-1558 - Grummitt, David, 1971- (Warfare in history., 2008)
'This is the book on the Calais garrison we have been waiting for'. COLIN RICHMOND. For over 200 years, following its capture by Edward III in 1347, the town of Calais was in English hands; after 1453 it remained the last English possession on the continent, a commercial, cultural, diplomatic and military frontier, until its recapture by the French in 1558. This book - the first full-length study so to do - examines the Calais garrison, the largest standing military force available to the English crown. Based on extensive archival research, it covers recruitment and service in the garrison, the problems of pay and logistics, the weaponry and tactics used, and the chivalric and professional ethos among the soldiers. It also investigates the effectiveness of English arms against their European counterparts, through a detailed study of the failed Burgundian siege of 1436 and the successful French siege of 1558. Overall, it reaffirms the importance of Calais to successive medieval and early modern English kings, and challenges the perceived notion that England lagged behind its northwest European rivals in terms of military technology and effectiveness. The Calais garrison is placed in the wider context of the development of European warfare in general during this period.' Dr DAVID GRUMMITT is Senior Research Fellow, History of Parliament Trust.